An investigiation of software holons- the 'adHOCS' approach - Maciaszek, Leszek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
This paper overviews our approach to application development using Holons, Objects, Components and Services (adHOCS) process, it explains the relevance of some modern software technologies to the adHOCS approach, and it presents a case study to measurably illustrate the adHOCS benefits. The holon abstraction – introduced by Arthur Koestler to interpret the structures and processes in living systems – is used to restrain software complexity. The adHOCS approach addresses the adaptiveness issue – namely that the software can adapt to changes and growth provided that better structuring and behavioural abstractions are used for the development and description of software systems. The paper shows that by superimposing the holon abstraction on application development methods, the resulting software systems display readily-understood structures that can accommodate the future growth while managing the underlying complexity
Argumenta Oeconomica, 2007, No 1-2 (19), s. 125-164
Keywords: Complex system; adaptive system; holon; holarchy; software architecture; composite pattern; Aspect-Oriented Programming; multi-agent systems; single-subject experimental design; software dependencies; software metrics